Logic for Programming, Artificial Intelligence, and Reasoning - Cervesato, Iliano (Springer, 2017)
This book constitutes the refereed proceedings of the 15th International Conference on Logic for Programming, Artificial Intelligence, and Reasoning, LPAR 2008, which took place in Doha, Qatar, during November 22-27, 2008.